Effect of Oil Fluctuation on Stock Market Return: An Empirical Study from India - Aggarwal, Priyanka; Manish, Manoj Kumar (International Journal of Energy Economics and Policy, 2020)
This paper examined the impact of oil price on Indian stock market. Data used for the study are monthly datasets from the period January 2000 to November 2018 obtained from Bombay Stock Exchange (BSE) and World Bank. BSE index is taken as dependent variable whereas oil price, inflation, exchange rate and real interest rate taken as independent variable. Augmented Dickey-Fuller (ADF) unit root test is used to make it certain that variables should be stationary as most of the economic data are non-stationary in nature. The Auto Regressive Distributed Lag (ARDL) model is used here and bound testing test method to cointegration is employed to test for long-run association among our time series dataset. Our finding shows that oil price changes have a significant as well as positive impact of Indian stock market return in both long run and short run. Impact of inflation and real interest rate have negative relationship with Indian stock market but insignificant for long run. Log of exchange rate have positive relation with Indian stock market, but it is also insignificant. Keywords: Oil Price, Stock Market Returns, Inflation, Exchange Rate JEL Classifications: D4, C22, E31, E4 DOI: https://doi.org/10.32479/ijeep.8802